Augmented Reality : Application in Higher Education : Final Report. - Munnerley, Danny; Bacon, Matt; Fitzgerald, Robert; Wilson, Anna; Hedberg, John; Steele, James (Office for Learning and Teaching, 2014)
Augmented reality offers opportunities to expand our concept of learning spaces, to create new dimensions to mobile learning and to increase connectedness of learners in multiple contexts. From simple systems where a tagged artifact reveals hidden images when viewed through a fixed web cam to interactive environments accessible from mobile devices allowing for communication and co-design, the technology for augmented reality is here now. Augmented reality is being embraced in marketing, the visual arts and in the museum sector. There is a real imperative for the education sector to experiment and find ways of using augmented reality to enhance student learning. This is the final report from a two-year project that developed effective uses of augmented reality in an educational context, together with tools for mapping its uptake and evaluating its effectiveness.